Evaluation Of Medical Waste Management Strategies In First Level Health Facilities: A Review From An Environmental Health Perspective - Saputra, Feri Surahman (Journal of International Public Health, 2024)
Public health centers as one of the institutions that produce medical waste have an obligation to maintain the environment and health in their working areas. Sumbersari Health Center has problems in handling solid medical waste at the stage of transportation and temporary storage. The purpose of this study is to determine how solid medical waste is handled at the stages of reduction, sorting, packaging, transportation, temporary storage, facilities and infrastructure as well as the knowledge and behavior of health workers and janitors. This study used descriptive method with purposive sampling technique. The sample size of Respondents amounted to 12 people and environmental samples amounted to 5 rooms that produce solid medical waste. The results of this study, obtained an average medical waste generation of 0.64 kg/day. Handling of medical waste at the reduction stage 75% meets the requirements, the sorting and packaging stage 100% meets the requirements, the transportation stage 20% meets the requirements, the temporary storage stage 87.5% meets the requirements, in facilities and infrastructure 75% meets the requirements. Aspects of knowledge and behavior of health workers are categorized as good 100%. The knowledge aspect of janitors is categorized as good 50% and sufficient 50%.The aspect of the behavior of janitors is categorized as 100% sufficient.It is advised that the health center add infrastructure for managing medical waste, such as trolleys for waste transportation, cold storage for waste kept longer than two days, scales, and instructions for cleaning staff on how to handle solid medical waste.